Distinguished fellow: Herbert Scarf's contributions to economics. - Arrow, Kenneth Joseph; Kehoe, Timothy Jerome (Journal of Economic Perspectives)
The election in 1991 of Herbert Scarf as a distinguished fellow of the American Economic Association honors the depth and diversity of his many contributions to studies of inventories, the core of economic theory, computation of equilibria, and integer programming. Scarf's work has always heavily influenced the way economists have learned to think about these subjects and sometimes led to flourishing lines of research. Scarf's career is traced, from his education at Temple and Princeton and early work at the Rand Corporation through teaching posts at Stanford and Yale, where he has held a post at the Cowles Foundation since 1963.